Industrial Image Processing Visual Quality Control in Manufacturing - Demant, Christian; Streicher-Abel, Bernd; Garnica, Carsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This practical introduction focuses on how to design integrated solutions for industrial vision tasks from individual algorithms. The book is now available in a revised second edition that takes into account the current technological developments, including camera technology and color imaging processing. It gives a hands-on guide for setting up automated visual inspection systems using real-world examples and the NeuroCheck® standard software that has proven industrial strength integrated in thousands of applications in real-world production lines. Based on many years of experience in industry, the authors explain all the essential details encountered in the creation of vision system installations. With example material and a demo version of the software found on "extras.springer.com" readers can work their way through the described inspection tasks and carry out their own experiments.
Introduction -- Overview: Image Preprocessing -- Positioning -- Overview: Segmentation -- Mark Identification -- Overview: Classification -- Dimensional Checking -- Overview: Image Acquisition and Illumination -- Presence Verification -- Overview: Object Features -- Outlook: Visual Inspection Projects -- A: Mathematical Notes -- B: The Companion CD -- References -- Index.
Keywords: Computer science; Computer vision; Computer Science; Image Processing and Computer Vision; Control, Robotics, Mechatronics; Signal, Image and Speech Processing